High Energy Density Laboratory Astrophysics - Lebedev, Sergey V.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
During the past decade, research teams around the world have developed astrophysics-relevant research utilizing high energy-density facilities such as intense lasers and z-pinches. Every two years, at the International conference on High Energy Density Laboratory Astrophysics, scientists interested in this emerging field discuss the progress in topics covering: - Stellar evolution, stellar envelopes, opacities, radiation transport - Planetary Interiors, high-pressure EOS, dense plasma atomic physics - Supernovae, gamma-ray bursts, exploding systems, strong shocks, turbulent mixing - Supernova remnants, shock processing, radiative shocks - Astrophysical jets, high-Mach-number flows, magnetized radiative jets, magnetic reconnection - Compact object accretion disks, x-ray photoionized plasmas - Ultrastrong fields, particle acceleration, collisionless shocks. These proceedings cover many of the invited and contributed papers presented at the 6th International Conference on High Energy Density Laboratory Astrophysics, which was held on March 11-14, 2006 at Rice University in Houston, Texas, USA.
Astrophysical jets, high-Mach-number flows, magnetized radiative jets, magnetic reconnection -- An Introduction to Observations Relevant to Astrophysical Jets and Nebulae -- Distinguishing Propagation vs. Launch Physics of Astrophysical Jets and the Role of Experiments -- Magnetic-Tower Jet Solution for Launching Astrophysical Jets -- 3D MHD Simulations of Laboratory Plasma Jets -- Outflow Propagation in Collapsars: Collimated Jets and Expanding Outflows -- Jet Deflection by a Quasi-Steady-State Side Wind in the Laboratory -- Hypersonic Swizzle Sticks: Protostellar Turbulence, Outflows and Fossil Outflow Cavities -- Plasma Jet Studies via the Flow Z-Pinch -- Double-Pulse Laser-Driven Jets on OMEGA -- Laboratory Modeling of Standing Shocks and Radiatively Cooled Jets with Angular Momentum -- Numerical Simulations and Astrophysical Applications of Laboratory Jets at Omega -- Laboratory Experiment of Plasma Flow Around Magnetic Sail -- Astrophysical Jets of Blazars and Microquasars -- Simulation of the Magnetothermal Instability -- Sheared Flow as a Stabilizing Mechanism in Astrophysical Jets -- How to Produce a Plasma Jet Using a Single and Low Energy Laser Beam -- Experimental Design for the Laboratory Simulation of Magnetized Astrophysical Jets -- Excitation of Electromagnetic Flute Modes in the Process of Interaction of Plasma Flow with Inhomogeneous Magnetic Field -- Plasma Jet Experiments Using LULI 2000 Laser Facility -- Magnetic Fields for the Laboratory Simulation of Astrophysical Objects -- Supernova remnants, shock processing, radiative shocks -- Assessing Mix Layer Amplitude in 3D Decelerating Interface Experiments -- The Formation of a Cooling Layer in a Partially Optically Thick Shock -- Measurement of the Growth of Perturbations on Blast Waves in a Mixed Gas -- Colliding Blast Waves Driven by the Interaction of a Short-Pulse Laser with a Gas of Atomic Clusters -- Investigating the Astrophysical Applicability of Radiative and Non-Radiative Blast wave Structure in Cluster Media -- Mass-Stripping Analysis of an Interstellar Cloud by a Supernova Shock -- Hydrodynamics of Supernova Evolution in the Winds of Massive Stars -- Theoretical and Experimental Studies of Radiative Shocks -- Electrostatic Potentials in Supernova Remnant Shocks -- Non-Stationary Rayleigh-Taylor Instabilities in Pulsar Wind Interaction with a Supernova Shell -- Compact object accretion disks, x-ray photoionized plasmas -- Phenomenological Theory of the Photoevaporation Front Instability -- Photoionized Flows from Magnetized Globules -- Nonlinear Dynamics of Ionization Fronts in HII Regions -- Pillars of Heaven -- The Evolution of Channel Flows in MHD Turbulence Driven by Magnetorotational Instability -- Laboratory Exploration of Solar Energetic Phenomena -- Explosion Mechanism of Core-Collapse Supernovae and Collapsars -- Stellar evolution, stellar envelopes, opacities, radiation transport -- Astrophysical Radiation Dynamics: The Prospects for Scaling -- Experiments to Study Radiation Transport in Clumpy Media -- Supernovae, gamma-ray bursts, exploding systems, strong shocks, turbulent mixing -- Laboratory Observation of Secondary Shock Formation Ahead of a Strongly Radiative Blast Wave -- Flash Code Simulations of Rayleigh-Taylor and Richtmyer-Meshkov Instabilities in Laser-Driven Experiments -- Models of Very-High-Energy Gamma-Ray Emission from the Jets of Microquasars: Orbital Modulation -- Time-Dependent Synchrotron and Compton Spectra from Microquasar Jets -- New Experimental Platform for Studies of Turbulence and Turbulent Mixing in Accelerating and Rotating Fluids at High Reynolds Numbers -- Weibel Turbulence in Laboratory Experiments and GRB/SN Shocks -- Diagnostics of the Non-Linear Richtmyer-Meshkov Instability -- Planetary Interiors, high-pressure EOS, dense plasma atomic physics -- Density Measurements of Shock Compressed Matter Using Short Pulse Laser Diagnostics -- Hydrogen and Helium at High Density and Astrophysical Implications -- Graded-Density Reservoirs for Accessing High Stress Low Temperature Material States -- He Conductivity in Cool White Dwarf Atmospheres -- The Structure of Jupiter, Saturn, and Exoplanets: Key Questions for High-Pressure Experiments -- Modeling Planetary Interiors in Laser Based Experiments Using Shockless Compression -- Ultrastrong fields, particle acceleration, collisionless shocks -- Scaling Laws for Collisionless Laser-Plasma Interactions of Relevance to Laboratory Astrophysics -- Topical Issues for Particle Acceleration Mechanisms in Astrophysical Shocks -- Three-Dimensional Particle Acceleration in Electromagnetic Cylinder and Torus -- Simulating Poynting Flux Acceleration in the Laboratory with Colliding Laser Pulses -- Three-Dimensional Particle Acceleration in Electromagnetic Dominated Outflows with Background Plasma and Clump -- 3-D RPIC Simulations of Relativistic Jets: Particle Acceleration, Magnetic Field Generation, and Emission -- Spectral Features of Photon Bubble Models of Ultraluminous X-ray Sources -- Polychromatic X-ray Beam from the Acceleration of Energetic Electrons in Ultrafast Laser-Produced Plasmas -- Scalable Dynamics of High Energy Relativistic Electrons: Theory, Numerical Simulations and Experimental Results -- Proton Radiography of Megagauss Electromagnetic Fields Generated by the Irradiation of a Solid Target by an Ultraintense Laser Pulse.
Keywords: Physics; Fluids; Astronomy; Astrophysics; Cosmology; Atoms; Matter; Plasma (Ionized gases).; Physics; Atomic, Molecular, Optical and Plasma Physics; Atoms and Molecules in Strong Fields, Laser Matter Interaction; Astrophysics and Astroparticles; Plasma Physics; Astronomy, Astrophysics and Cosmology; Fluid- and Aerodynamics; Electronic books